Histone H3K9 Trimethylation Downregulates the Expression of Brain-Derived Neurotrophic Factor in the Dorsal Hippocampus and Impairs Memory Formation During Anaesthesia and Surgery - Wu, Tong; Sun, Xiao-Yu; Yang, Xiu; Liu, Le; Tong, Kun; Gao, Ya; Hao, Jing-Ru; Cao, Jing; Gao, Can (Frontiers in Molecular Neuroscience, 2019)
The BDNF is essential in cognition and memory. Abnormal BDNF expression in central nerve system may result in cognition and memory attenuation. Anesthesia and surgery may induce perioperative neurocognitive disorders (PND). Clinical studies show that the BDNF expression is decreased in patients suffering the cognitive impairment after anesthesia and surgery. However, the neuropathogenesis remains largely unknown. The epigenetic regulation plays an important role in cognition. Hypermethylation of H3K9 is relevant to transcriptional silence and cognitive disorder. Here, we hypothesized that the H3K9 trimethylation repressed BDNF expression and impaired memory formation or recall during anesthesia and surgery. Laparotomy under isoflurane inhalation anesthesia model, various behavioral tests, western blotting, quantitative real-time reverse transcription polymerase chain reaction, chromatin immunoprecipitation and immunohistochemistry were used in this study. We found that the BDNF expression was decreased in hippocampus after anesthesia and surgery. The cognition impairment affected memory acquisition instead of recall. Trimethylation of H3K9 induced the repression of BDNF. Overexpression of BDNF or complement of exogenous BDNF rescued the acquisition of memory after anesthesia and surgery. Inhibiting H3K9 trimethylation and improving the expression of BDNF could avoid PND for clinical applications.